2017
DOI: 10.1111/pan.13172
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of gastric emptying after breakfast in healthy preschool children

Abstract: The results of the balloon experiment showed a high correlation between balloon antral area and balloon volume. In the preschool child measurements, gastric antral area correlated with fasting time, and the mean gastric emptying time was lower than 4 hours after breakfast. These results support a more liberal perioperative fasting regimen after a light meal or breakfast in routine pediatric anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
1
29
2
1
Order By: Relevance
“…To overcome these problems, more liberal fasting regimens and better interdisciplinary cooperation would be beneficial. Andersson et al showed that dispensing with the 2 hours fasting limit for clear fluids was not associated with an increased incidence of pulmonary aspiration, and other studies found that the stomach processes a light meal in less than 4 hours . For a better implementation of improved fasting regimens, Newton et al favored a structured quality improvement program leading to an increased proportion of children fasting less than 4 hours after the introduction of a standard operating procedure checking the fasting status on admission and allowing clear fluids up to 1 hour before anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome these problems, more liberal fasting regimens and better interdisciplinary cooperation would be beneficial. Andersson et al showed that dispensing with the 2 hours fasting limit for clear fluids was not associated with an increased incidence of pulmonary aspiration, and other studies found that the stomach processes a light meal in less than 4 hours . For a better implementation of improved fasting regimens, Newton et al favored a structured quality improvement program leading to an increased proportion of children fasting less than 4 hours after the introduction of a standard operating procedure checking the fasting status on admission and allowing clear fluids up to 1 hour before anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Andersson et al 3 showed that dispensing with the 2 hours fasting limit for clear fluids was not associated with an increased incidence of pulmonary aspiration, and other studies found that the stomach processes a light meal in less than 4 hours. 6 Children with an expected waiting time of more than 4 hours should receive a standardized light meal in the morning. 7 In addition, all infants and children should be allowed to drink clear fluids liberally up to 1 hour before anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O POCUS para avaliação do conteúdo gástrico pode ser usado para sustentar uma rotina mais liberal no jejum pré-operatório de crianças. No artigo de Sumpelmann et al 28 , foi conduzido um estudo observacional e experimental. Balões em formato de pera eram preenchidos com 500 mL de água e esvaziados em incrementos de 50 mL.…”
Section: O Manejo Das Vias Aéreasunclassified